2020
DOI: 10.1002/jbmr.4279
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Osteomyelitis: Marrying Bone Biology and Microbiology to Shed New Light on a Persistent Clinical Challenge

Abstract: Infections of bone occur in a variety of clinical settings, ranging from spontaneous isolated infections arising from presumed hematogenous spread to those associated with skin and soft tissue wounds or medical implants. The majority are caused by the ubiquitous bacterium Staphyloccocus (S.) aureus, which can exist as a commensal organism on human skin as well as an invasive pathogen, but a multitude of other microbes are also capable of establishing bone infections. While studies of clinical isolates and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 95 publications
0
12
0
1
Order By: Relevance
“…As a result of its great density from calcification, bone has unique pharmacodynamic challenges for drug targeting, including antibiotic treatments. While the major clinical challenges in curing chronic osteomyelitis are well known, the futility of so called “local” antibiotic therapy achieved from placing a high concentration of drug proximal to the infection in ALBC has become a great topic of debate, as there are no clinical studies that have demonstrated efficacy over systemic antibiotic therapy alone, and the costs of ALBC have been called into question [ 23 ]. Moreover, the seminal in vivo rabbit study of Giers et al [ 39 ], which demonstrated that MRI contrast agents similar in size and solubility to common antimicrobials mixed with bone cement are transported away from the bone lesion, suggests that interstitial fluid convection thwarts such “local” antibiotic therapies, as illustrated in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of its great density from calcification, bone has unique pharmacodynamic challenges for drug targeting, including antibiotic treatments. While the major clinical challenges in curing chronic osteomyelitis are well known, the futility of so called “local” antibiotic therapy achieved from placing a high concentration of drug proximal to the infection in ALBC has become a great topic of debate, as there are no clinical studies that have demonstrated efficacy over systemic antibiotic therapy alone, and the costs of ALBC have been called into question [ 23 ]. Moreover, the seminal in vivo rabbit study of Giers et al [ 39 ], which demonstrated that MRI contrast agents similar in size and solubility to common antimicrobials mixed with bone cement are transported away from the bone lesion, suggests that interstitial fluid convection thwarts such “local” antibiotic therapies, as illustrated in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, S. aureus within the OLCN is a permanent reservoir of bacteria that cannot be eradicated by host responses or any known treatments short of amputation [ 9 , 20 , 21 , 22 ]. While in vivo bromodeoxyuridine labeling studies in mice have demonstrated that orally administered small molecules have access to S. aureus at the leading edge of the colony within the OLCN [ 17 ], we have also shown that both methicillin-sensitive S. aureus (MSSA) [ 23 ] and methicillin-resistant S. aureus (MRSA) [ 24 ] OLCN invasion cannot be prevented or eradicated by combined high-dose local and systemic antibiotics, likely due to its well-known adaptive responses that are associated with persister cells and small colony variants (SCVs) [ 10 ]. Thus, OLCN invasion might limit the availability of conventional antibiotics to levels below the minimum inhibitory concentration (MIC) and minimum biofilm eradication concentration (MBEC), and therefore activates biological mechanisms of antibiotic tolerance, such as the doubling of the bacterial cell wall thickness that we observed [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the numerous in vitro research on antimicrobial efficacy is carried out in the experimental settings and performed in the conventional microbiological broths. The molecular composition of these media is rich in polysaccharides, peptides, amino acids, and glucose, which in turn are scantily present at the site of bone infection [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many bacterial pathogens have been etiologically associated with osteomyelitis, Staphylococcus aureus is overwhelmingly the most common cause and the pathogen that causes the most damage to the bone and surrounding tissues [1][2][3]. Osteomyelitis is a uniquely problematic form of S. aureus infection owing to its complex pathology and intrinsic resistance to conventional antibiotic therapy [4,5].…”
Section: Introductionmentioning
confidence: 99%